2022
DOI: 10.1097/bot.0000000000002366
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Comparison of Splinting Constructs for Distal Radius Fractures: An Effort to Free the Elbow

Abstract: Objectives: To compare short-term functional outcomes, reduction loss, and rates of surgery for distal radius fractures initially immobilized with a traditional sugar-tong splint versus clamshell splint freeing the elbow.Design: Prospective randomized trial.Setting: Level 1 trauma center.Patients: Eighty-nine consecutive patients sustaining distal radius fractures were enrolled between 2018 and 2020. Short-term first follow-up (1-2 weeks) radiographic parameters and 6 weeks for functional questionnaires were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…They also reported no differences in radiographic outcomes or treatment failure (either loss of reduction or requirement for surgical intervention). The present study supplements the data reported in these reviews by incorporating articles published within the last two years, including studies conducted by Dib et al [ 14 ] and Stevens et al [ 19 ], which collectively constitute over one-third of the cases included in this review. In summary, the current literature leans toward equivocal results regarding the use of SA versus LA immobilization constructs.…”
Section: Reviewmentioning
confidence: 67%
See 2 more Smart Citations
“…They also reported no differences in radiographic outcomes or treatment failure (either loss of reduction or requirement for surgical intervention). The present study supplements the data reported in these reviews by incorporating articles published within the last two years, including studies conducted by Dib et al [ 14 ] and Stevens et al [ 19 ], which collectively constitute over one-third of the cases included in this review. In summary, the current literature leans toward equivocal results regarding the use of SA versus LA immobilization constructs.…”
Section: Reviewmentioning
confidence: 67%
“…[ 14 ] to 22% as reported by Stevens et al. [ 19 ]. Another limitation is the difference in methods used to describe and classify fracture patterns.…”
Section: Reviewmentioning
confidence: 83%
See 1 more Smart Citation
“…In a study of 89 patients randomized to a sugar-tong splint or a clam-shell splint, equivalent DASH scores, loss of reduction rates, and surgical conversion were reported. Thus, avoiding elbow immobilization appears to be safe and may minimize elbow stiffness, although this study did not measure the final elbow range of motion 9 .…”
Section: Distal Radius and Wristmentioning
confidence: 95%